Receptor activity-modifying protein modulation of parathyroid hormone-1 receptor function and signaling - Avgoustou, Paris; Jailani, Ameera B. A.; Desai, Aditya J.; Roberts, David J.; Lilley, Ewan R.; Stothard, Grant W.; Skerry, Timothy M.; Richards, Gareth O. (Frontiers in Pharmacology, 2024)
Receptor activity-modifying proteins (RAMPs) are known to modulate the pharmacology and function of several G protein-coupled receptors (GPCRs), including the parathyroid hormone 1 receptor (PTH1R). However, the precise effects of different RAMPs on PTH1R signalling and trafficking remain poorly understood. Here we investigated the impact of RAMP2 and RAMP3 on PTH1R function using a range of PTH-and PTH-related protein (PTHrP)-derived ligands.FRET imaging revealed that PTH1R preferentially interacts with RAMP2 and, to a lesser extent, RAMP3, but not RAMP1. Interestingly, RAMP3 co-expression resulted in reduced cell surface expression of PTH1R, suggesting a potential role in receptor trafficking or internalization. The presence of RAMP2 significantly enhanced PTH1R-mediated cAMP accumulation, β-arrestin recruitment, and calcium signalling in response to PTH (1-34), PTHrP (1-34), PTH (1-84), and the PTH (1-17) analogue ZP2307. In contrast, RAMP3 co-expression attenuated or completely abolished those responses.We found that full-length PTHrP analogues, PTHrP (1-108) and PTHrP (1-141), exhibited lower potency and efficacy than PTHrP (1-34) in activating PTH1R. RAMP2 significantly increased potency and/or efficacy when compared to PTH1R alone cells, while RAMP3 significantly reduced these responses. Antibody-capture scintillation proximity assays demonstrated that RAMP2 differentially modulates G protein activation by PTH1R in a ligand-dependent manner, with PTH (1-34) and PTHrP (1-34) inducing distinct patterns of G protein subtype activation.These findings highlight the complex role of RAMPs in regulating PTH1R signalling and trafficking, revealing differential effects of RAMP2 and RAMP3 on receptor function. The data suggest that targeting the PTH1R/RAMP2 complex may be a promising strategy for developing novel bone anabolic therapies by leveraging biased agonism and functional selectivity.